Lampanah Local Tall-A High Yielding Variety for Replanting Coconut in Tsunami Affected Aceh Province Area - Novarianto, Hengky; Maskromo, Ismail; Tulalo, Meity A.; Kumaunang, Jeanette; Mawardi, Sukmawati; Sulistyowati, Emy (International Coconut Community Journal, 2017)
Aceh province is one of major coconut producing areas in Indonesia. In 2013 coconut areas in Aceh province was 107,654 ha in which total production of copra was equivalent to 63,743 tons. The entire coconut area in Aceh belong to smallholders. The coconut production in this area began to decrease in 2005 by an average of 9 percent per year, which was mainly caused by the tsunami. This had resulted in damage to many crops. Efforts to increase production and productivity of coconut plantation in Aceh needed rejuvenation of the old or unproductive coconut palms with the use of seeds of improved quality. Based on the results of the research conducted during 2014-2016, it is known that the origin of the Lampanah tall is passed from generation to generation and is a native of coconut in Aceh Besar Regent, Aceh Province. The morphology of Lampanah tall coconut comprising of the crown of leaves, stems, flowers and fruits in general is quite uniform. Of the data on the 23 quantitative characters, all have a value of coefficient of variance below 20%, except the character of 11 leaf scars obtained 23.29%. In the case of polar girth, Lampanah tall coconut is generally greater than the equatorial girth, fruit shape classified as round, egg-shaped and elliptic. The seednut of Lampanah tall generally round shape. The Lampanah tall coconut has the number of bunches at 13.35/palm and the number of fruit at 9.25 fruits/bunch or an average of 138 fruits/palm/ year. Fresh coconut meat weight is 449 g/nut or approximately 224 g copra/nut and the potential for copra production was 30.97 kg/palm/year or 3.80 tons of copra/ha/year. The fat content of Lampanah tall coconut was 66.40%, the water content of copra approximately 3.42% and protein at approximately 6.81%. Total saturated fatty acids was at 94.27%, medium chain saturated fatty acids at 67.21% and lauric acid content at 46.50%. The seed source of Lampanah tall coconut has been a selection of as much as 72 Selected Mother Palms (MAS) from a total of 407 palms of the High Yielding Block. The selected population is characterised with traits like copra yield more than 2.0 ton/ha/year, free from attack pests and diseases, number of bunch more than 12 per year, total nuts more than 7/bunch and weight of meat more than 400 g/nut. The MAS of Lampanah tall whole coconut has been marked using GPS. The Aceh government will build a minimum of 5 ha Coconut tall Seed Gardens on government land, as the development of source of Lampanah tall seednuts. Based on the above results, it can be concluded that the Lampanah tall coconut with plenty of nuts, at an average of 138 nuts per palm could be released as one of the national high yielding coconut.